Phyllomedusa: taxonomic status, habits, and biology (Amphibia, Anura, hylidae) - Caramaschi, Ulisses; Cruz, Carlos Alberto Gonçalves (Phyllomedusa: Journal of Herpetology, 2002)
Diagnosis for the Hylidae family of tree-frogs, and diagnosis and included genera for the four subfamilies currently in this family, Hcmiphractinae, Hylinae, Pelodryadinae, and Phyllomcdusinae, are provided. The genera of the Phyllomedusinae subfamily, Agalychnis, Hylomantis, Pachymedusa, Phasmahyla, Phrynomedusa, and Phyllomedusa, are diagnosed and the species included and their geographical distribution are referred. Notes on the habits and biology of members of the genus Phyllomedusa are presented.